Synthesis of α-CF3-proline derivatives by means of a formal (3 + 2)-cyclisation between trifluoropyruvate imines and Michael acceptors. Issue 23 (31st May 2019) - Winter, Michael; Faust, Kirill; Himmelsbach, Markus; Waser, Mario
Abstract : The first (3 + 2)-cyclisation of 3, 3, 3-trifluoropyruvate-derived imines and indandione-based Michael acceptors giving spirocyclic α-CF3 -α-proline derivatives was developed. Abstract : We herein report the first formal (3 + 2)-cyclisation between 3, 3, 3-trifluoropyruvate-derived imines and indandione-based Michael acceptors. This reaction gives access to a novel class of spirocyclic α-CF3 -α-proline derivatives with complete control of the diastereoselectivity under phase transfer-catalysed reaction conditions.